2022
DOI: 10.1007/s10067-022-06366-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of laboratory predictors for intravenous immunoglobulin resistance and coronary artery aneurysm in Kawasaki Disease before and after therapy

Abstract: Objectives We aimed to evaluate the clinical and laboratory characteristics of patients with Kawasaki disease (KD) before and after therapy. Methods Patients with KD were divided into different groups according to their responsiveness to initial intravenous immunoglobulin (IVIG) treatment and coronary status. The clinical and laboratory parameters before and after therapy were compared. Multivariate analysis was performed to identify the independent risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Although missing data and the small sample size (persistent CAA group) prevented us from investigating the role of sampling-time-specific PNI cutoff values in predicting persistent CAA, these findings provide important evidence regarding the discrepancies in the predictive values for IVIG resistance and CAA development by the same parameter. Interestingly, the lowest PNI value in both the persistent CAA and the normal groups occurred on day 6, which is consistent with the results of our previous studies and other reports ( 23 , 58 60 ). Thus, pediatricians and cardiovascular specialists should focus not only on patients with CAA with a higher maximum Z -score at 1 month after onset, but also on patients with low PNI levels, as these can predict persistent CAA within a few days after illness onset.…”
Section: Discussionsupporting
confidence: 93%
“…Although missing data and the small sample size (persistent CAA group) prevented us from investigating the role of sampling-time-specific PNI cutoff values in predicting persistent CAA, these findings provide important evidence regarding the discrepancies in the predictive values for IVIG resistance and CAA development by the same parameter. Interestingly, the lowest PNI value in both the persistent CAA and the normal groups occurred on day 6, which is consistent with the results of our previous studies and other reports ( 23 , 58 60 ). Thus, pediatricians and cardiovascular specialists should focus not only on patients with CAA with a higher maximum Z -score at 1 month after onset, but also on patients with low PNI levels, as these can predict persistent CAA within a few days after illness onset.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, neutrophil-tolymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been confirmed for their discriminative abilities to predict IVIGresistant KD patients in previous reports (35,36). This research indicated that PNI is at its lowest on the 6th day of disease onset, while SII is at its highest, demonstrating that both PNI and SII exhibit good predictive capabilities for KD with IVIG resistance on the 6th day of the disease course (33). The combined diagnosis of these two markers may enhance the diagnostic accuracy for KD with IVIG resistance, which is consistent with another study (16).…”
Section: Discussionsupporting
confidence: 58%
“…Currently, an increasing number of studies are emerging regarding the diagnostic and prognostic value of PNI in various diseases. A previous meta-analysis investigated the value of PNI in the prognosis of cardiovascular diseases and showed that PNI can independently (17,33,34). In addition, neutrophil-tolymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been confirmed for their discriminative abilities to predict IVIGresistant KD patients in previous reports (35,36).…”
Section: Discussionmentioning
confidence: 95%
“…A correlation between B/A ratio levels and bilirubin encephalopathy has been shown, with higher B/A ratios increasing the bilirubin encephalopathy risk by 23% [ 36 ]. In addition, a high B/A ratio can predict resistance to intravenous immunoglobulin in patients at high risk for Kawasaki disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%